2023
DOI: 10.3390/foods12091859
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Polymeric Microparticles Using Eco-Friendly Extracted Crude Fucoidans from Edible Brown Seaweed Undaria pinnatifida

Abstract: Several bioactive compounds that hold a potential interest in the food industry as phenolic compounds, polysaccharides, proteins and vitamins, among others, are present in seaweeds. Green extraction technologies are the preferred way to obtain these compounds. Pressurized hot water extraction, from 160 to 220 °C, was tested to achieve high yields of these components from the edible brown seaweed, Undaria pinnatifida. The maximum fucoidan content was recovered at 160 °C, while the phloroglucinol content and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The authors reported that the use of SFE to produce Spirulina extracts can lead to extracts with a higher content of valuable components such as fatty acids, phenolic compounds, minerals, pigments, etc. However, they also pointed out that special attention should be paid to the extraction yield of potentially harmful components, such as heavy metals.Ferreira-Anta et al [4], on the other hand, tested the effects of different temperatures (from 160 to 220 °C) in pressurized hot water extraction on the yield and profile of extracted bioactive components (proteins, fucoidan, phloroglucinol, carbohydrates, sulfates, etc.) from the edible brown alga Undaria pinnatifida.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported that the use of SFE to produce Spirulina extracts can lead to extracts with a higher content of valuable components such as fatty acids, phenolic compounds, minerals, pigments, etc. However, they also pointed out that special attention should be paid to the extraction yield of potentially harmful components, such as heavy metals.Ferreira-Anta et al [4], on the other hand, tested the effects of different temperatures (from 160 to 220 °C) in pressurized hot water extraction on the yield and profile of extracted bioactive components (proteins, fucoidan, phloroglucinol, carbohydrates, sulfates, etc.) from the edible brown alga Undaria pinnatifida.…”
mentioning
confidence: 99%
“…In this context, this SI consists of six original research papers [ 1 , 2 , 3 , 4 , 5 , 6 ] and two review papers [ 7 , 8 ] that address recent advances and current knowledge in the proposed field.…”
mentioning
confidence: 99%
See 1 more Smart Citation